Enhancing emotional intelligence for well-being in higher education: Supporting SDG 3 amid adversity - Prashanti Maharaj; Anisha Ramsaroop (SA Journal of Human Resource Management)
Orientation: The coronavirus disease 2019 necessitated tertiary institutions to reevaluate their educational paradigms, emphasising resilience and fostering creative mindsets to navigate unprecedented challenges. This disruption evoked distressing emotions, posing threats to academics’ emotional well-being. Such challenges carry profound implications for the attainment of sustainable development goal 3 (SDG 3), aimed at ensuring healthy lives and promoting well-being for all.